What Drives Student Recommendations? : An Empirical Investigation of the Learning Experiences of International Students in Australia, the UK, and the US - Dennis, John L.; Ammigan, Ravichandran (Journal of Interdisciplinary Studies in Education, 2022)
Insights into how student learning experiences impact university recommendation can be critical for higher education institutions as they seek to optimize enrollment and retention efforts in an increasingly competitive and highly unpredictable global market. This comparative study examines the extent to which satisfaction with various aspects of the academic environment influences recommendation for over 23,000 international undergraduate students at universities in Australia, the United Kingdom, and the United States. Five key implications for the quality of teaching and learning, English language support, career development and readiness, access to information and communication technologies, and assessment and benchmarking are discussed. Results from a factor analysis reveal an underlying structure to the learning variables used in this research and provide empirical support for its application in future investigations of the academic experiences of international students in higher education.